Main Determinants of PON1 Activity in Hemodialysis Patients - Ribeiro, Sandra (2012)
Cardiovascular diseases are the major cause of morbidity and mortality in hemodialysis (HD) patients. These patients present reduced paraoxonase 1 (PON1) activity that depends on genetic and non-genetic factors; however, how these factors influence PON1 activity in HD patients is poorly clarified. Our aim was to evaluate the influence of two polymorphisms and non-genetic factors on PON1 activity in HD patients.